Process parameter studies by central composite design of response surface methodology for production of biosurfactant by Escherichia coli khodavandi-alizandeh-2 isolated from hydrocarbon contaminated soil - Osho, Michael; Ajiboye, Joy (Food and Applied Bioscience Journal, 2022)
Biosurfactants synthesized by microorganisms are surface-active secondary metabolites that have gained industrial significance due to their interfacial tension-reducing properties. Hydrocarbon-polluted soils have proved a major habitat of biosurfactant-producing bacteria. This study explored the isolation of bacteria from petroleum contaminated soil and optimization of process parameters for biosurfactant production from Escherichia coli Khodavandi-Alizandeh-2 using response surface methodology (RSM) of Design Expert. Bacterial isolates were screened for biosurfactant production on mineral salt medium containing 1% automobile oil using various screening procedures (hemolysis test, oil displacement test, bacteria adhesion to hydrocarbon and emulsification assay). Parameter conditions (temperature, pH, carbon source, nitrogen source, agitation and inoculum quantity) were optimized for maximum biosurfactant yield. From several bacteria screened only one showed maximum hemolytic activity, 55% bacterial adhesion, and 50% emulsification activity. Molecular evolutionary genetic analysis of the isolate using 16S RNA gene sequence revealed to be Escherichia coli Khodavandi-Alizandeh-2. The optimization studies revealed that optimal biosurfactant production was obtained at 30°C temperature,2 g glucose, 3 g yeast extract, 150 rpm Agitation, 2 mL inoculum quantity and pH 7. RSM further revealed that an increase in temperature at reduced pH will increase biosurfactant yield. The main chemical constituent of the biosurfactant produced as unveiled by Gas Chromatography Mass Spectrometry was Pyrrolo[1,2]pyrazine-1,4-dione, hexahydro-3-(phenylmethyl) (63.22%). This research can find applicationsin bioremediation and hydrocarbon degradation.